PARTICLE SWARM OPTIMIZATION (PSO) ALGORITHM BASED CONTROLLER FOR DC SERVOMOTOR - MUNIANDY, GUNALAN (2014)
Proportional, Integral and derivative (PID) controllers are the most widely-used controller in many industrial applications because of their simplicity, robustness and successful practical application. However, the major drawback of PID controllers is that most of the tuning is done manually as they are poorly tuned in practice which leads too much difficulty and also time consuming. Although many tuning methods have been proposed for PID controllers, this research explores the potential use of intelligent algorithms in controllers and their advantages over conventional methods. This thesis asserts that the conventional approach of PID tuning is not very efficient due to the presence of non-linearity in the system of the plant. The output of the conventional PID system has a quite high overshoot and settlingtime.